صدى القراءة الغربية للنص الرشدي في بعض القراءات العربية المعاصرة - مهلوبي, برهان; صبيح, وسيم (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يعنى هذا البحث بالوقوف على جملة من القراءات العربية للنصوص الفلسفية الرشدية، وإبراز مدى تأثرها بالقراءات والمناهج التي اتبعها الباحثون الغربيون. فعلى الرغم من الأبعاد الإيديولوجية للدراسات الاستشراقية إلا أنها فتحت لنا آفاقاً جديدة، ومهّدت لمداخل أَثْرَت مداخلنا نحو تناول النصوص الرشدية، كما شكلت تحديات فكرية لا بد لنا من مواجهتها معرفياً لا مُجرَّد اتهامها بالتحامل والانتقائية.نحاول في هذا البحث الوقوف على الأسباب التي جعلت القراءات العربية لفيلسوف قرطبة تختلف من باحث إلى آخر إلى حد المباينة بالمجمل في بعض الأحيان.This study aims to an alyzesome of the Arabic readings of the philosophical texts of Ibn Rushd and to demonstrate their influence on the ones that western researchers have followed. In spite of the ideological dimensions of oriental studies, they opened new horizons and introduced approaches that affected the way we deal with Rushditexts. Moreover. they have presented intellectual challenges that must be dealt with cognitively, not only with a prejudiced selective manner.The researcher tries to point out to the reasons which made the Arabic readings for Cordoba differ from one researcher, sometimes to the extent of complete opposition.